2020
DOI: 10.1002/mabi.202000256
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Bone‐Mimetic Scaffold Composed of Gelatin/β‐Tri‐Calcium Phosphate for Bone Tissue Engineering

Abstract: biodegradable polymer scaffolds were widely studied for bone regeneration because the metal implants have the limitations of non-degradability and high rigidity. [2,3] Common methods for fabricating such a scaffold include particulate leaching, electrospinning, and freeze-drying. However, these methods have limited reproducibility and versatility in their manufacturing processes. [4] To solve these problems, the 3D bioprinting technology for making scaffolds by stacking printing materials has been applied. [5]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…We further examined the GR scaffold via H&E, Masson’s trichrome (MT), and von Kossa staining (VK) and found it could promote bone regeneration and bone formation effectively in vivo [ 48 ]. Consistent with the in vitro results, H&E staining indicated that the hard tissue morphology presented more tibia integrity in the G5 scaffold groups than the G0 scaffold [ 49 ]. MT and VK staining also showed that collagen and calcification were increased in the G5 scaffold after 4 and 8 weeks of implantation.…”
Section: Resultssupporting
confidence: 71%
“…We further examined the GR scaffold via H&E, Masson’s trichrome (MT), and von Kossa staining (VK) and found it could promote bone regeneration and bone formation effectively in vivo [ 48 ]. Consistent with the in vitro results, H&E staining indicated that the hard tissue morphology presented more tibia integrity in the G5 scaffold groups than the G0 scaffold [ 49 ]. MT and VK staining also showed that collagen and calcification were increased in the G5 scaffold after 4 and 8 weeks of implantation.…”
Section: Resultssupporting
confidence: 71%
“…Moreover, the FTIR analysis did not reveal any significant change between α-TCP alone and the composite. The peak for GS (1631 cm −1 ) slightly shifted to a higher wave number (1640 cm −1 ) in the α-TCP/GS, due to the electrostatic interaction between calcium ions in α-TCP and carboxyl groups in gelatin [25,26].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, they demonstrated, using a rat model, that fabricated novel 3D printed biomaterial enhanced bone formation. In another study, Jeong et al [62] showed that 3D printed bone scaffolds containing gelatin and β-TCP were supportive to preosteoblasts' (MC3T3-E1 cells) adhesion, proliferation, and differentiation in vitro. Moreover, the scaffold stimulated bone formation in the animal experiments (a rat model).…”
Section: Three-dimensional Bioprintingmentioning
confidence: 99%